Pt–Cu based nanocrystals as promising catalysts for various electrocatalytic reactions. Issue 29 (8th July 2019) - Chaudhari, Nitin K.; Hong, Yongju; Kim, Byeongyoon; Choi, Sang-Il; Lee, Kwangyeol
Abstract : This review addresses recent developments in Pt–Cu based catalysts toward various energy conversion electrocatalytic applications such as the HER, ORR, MOR, EGOR and FAOR. Abstract : Taking into account availability and cost, the development of Pt bimetallic alloy nanocatalysts containing earth abundant elements is of vital interest in advancing technologies that depend on electrocatalytic reactions. In this regard, a number of studies on Pt–Cu based alloy nanocrystals have been performed for various electrocatalytic oxidation/reduction reactions owing to their novel physico-chemical properties. Herein, we present an in-depth review on recent developments in Pt–Cu based nanostructures from the viewpoint of electrocatalysts for various reactions. In this review, the synthesis methodologies and composition- and morphology-dependent catalytic properties of Pt–Cu based electrocatalysts are extensively discussed and summarized. The insights into the remaining challenges and the directions for future research on Pt–Cu electrocatalysts are also highlighted for practical applications in renewable energy systems.